Vejrforholdene i Landbrugsaaret 1892—93. (Fra 1. Oktober 1892 til 30. September 1893). - Willaume-Jantzen, V. (Tidsskrift for Landøkonomi, 2018)
Vejrforholdene i Landbrugsaaret 1892—93. (Fra 1. Oktober 1892 til 30. September 1893).